(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This qualitative study aims to analyze the Buyi Tonggu Shuaba Dance and its role in the context of ethnic minority identity in China. The research method involves collecting, analyzing, and studying relevant literature. The researcher conducted field work in Zhouqin Town, Sandu County, Qiannan Buyi and Miao Autonomous Prefecture, Guizhou Province China. The research conclusions of this paper were drawn through descriptive analysis. The research objectives are as follows: • To explore the history and significance of Guizhou Buyi Tonggu Shuaba Dance; 2) To analyze the performance structure and current practices of Tonggu Shuaba Dance from a localism perspective. The findings are presented as follows: 1)The Guizhou Buyi Tonggu Shuaba Dance has undergone four key historical stages, and the evolution of the Tonggu Shuaba Dance is intertwined with Buyi culture. The research explores the social role of the Buyi people during different periods, considering factors such as their living environment, culture, and history. 2) The study examines the artistic components of the Buyi Tonggu Shuaba Dance, and summarizes the characteristics of the performance of Tonggu Shuaba Dance in terms of form, props, and rhythm. Additionally, the current practice status of the Tonggu Shuaba Dance in Zhouqin Town, Guizhou Province is analyzed. This research is beneficial for strengthening the cultural identity and self-confidence of the Buyi Tonggu Shuaba Dance in Guizhou, and supporting its continued transmission and development in contemporary society.